Comparison of margin assessment between intraoperative digital and conventional specimen mammography in breast cancer: A preliminary study - Heejung Keum; Ho Yong Park; Byeongju Kang; Jin Hyang Jung; Wan Wook Kim; Jeeyeon Lee (Asian Journal of Surgery, 2023)
Background: Although breast surgeons can request frozen section biopsies to evaluate margin status in breast-conserving surgery (BCS), specimen imaging is also a useful assessment tool. Intraoperative digital specimen mammography (IDSM) has recently been introduced in Korea. To estimate the clinical role of IDSM, this study compared the clinicopathologic factors of patients whose specimen was assessed with IDSM with those assessed using conventional specimen mammography (CSM). Methods: From October to December 2021, 78 breast cancer patients who underwent BCS were included in this study. The obtained specimens were assessed using IDSM (n = 44) and CSM (n = 34). Clinicopathologic factors included margin involvement status in specimen mammography and the results of frozen section biopsies. The radiation dose emitted from the specimen after mammography was measured using a portable device. Results: There were no significant differences in clinicopathological factors between the two groups, except the type of surgery for axillary lymph nodes. The closest distance from the margin to tumor was longer in the CSM group than in the IDSM group, although the difference was not statistically significant (p = 0.894). Margin involvement was accurately detected using IDSM due to the absence of compression (p < 0.001). In addition, the sensitivity and accuracy of IDSM were higher, and the false-negative rate was lower. Conclusion: Both specimen mammography methods were highly accurate in evaluating the margin involvement status. However, the margin status could be examined more precisely using IDSM because the specimen was not compressed to perform the examination. Because the IDSM system was installed in the operating room, it not only shortened performing routes but also reduced the operating time by providing immediate results.